Effect of Brown Rice Intervention on BMI and Waist Circumference in Patients with Type 2 Diabetes Mellitus - Endang Sutjiati; Etik Sulistyowati; Dea Intan Permatasari (Indonesian Journal of Human Nutrition, 2023)
Brown rice, derived from white rice with the removal of the husk, contains higher dietary fiber and a lower glycemic index than regular white rice. These advantages can be an alternative diet for individuals with type 2 diabetes mellitus. Type 2 diabetes mellitus is a metabolic disease ranked as the fourth leading cause of death in the world, often associated with obesity. In addition, insulin insensitivity in individuals with type 2 diabetes leads to increased hunger (polyphagia) and overeating, resulting in increasing BMI and waist circumference. The purpose of this study is to determine the effect of the brown rice diet intervention on BMI and waist circumference of patients with type 2 diabetes. This study was a pre-experimental study without control variables and the sample was not selected randomly, using a one-group pretest-posttest design with a 3-month intervention. Data analysis in this study used the Shapiro-Wilk normality test followed by the paired t-test to determine the difference between two paired samples. The statistical results showed significant changes in BMI and abdominal circumference (p = 0.002 and p = 0.008, respectively). In conclusion, there are differences in BMI and abdominal circumference of patients with type 2 diabetes mellitus before and after the intervention of a brown rice-based diet menu.